2020
DOI: 10.21203/rs.2.23036/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of KIF23 as a prognostic signature for ovarian cancer based on large scale samples and clinical validation

Abstract: Background: Ovarian cancer is one of the common malignant tumors in gynecology. Although the treatment strategy for ovarian cancer has been greatly improved in recent years, due to the metastasis, recurrence and drug resistance, the 5-year overall survival rate of patients is still less than 47%. However, at present, there is no specific markers for clinical application. The purpose of this study is to verify the expression and clinical significance of KIF23 in ovarian cancer and identify potential targets for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Meanwhile, they also found that both miR-503-5p and miR-424-5p could directly targeted KIF23 to inhibit OC development in vitro [ 69 ]. Additionally, Hu Y et al has reported that KIF23 could not only be used as a prognostic indicator for EOC, but also had a positive correlation with immune checkpoint protein, suggesting that it can be performed as a potential target for cancer immunotherapy, which is consistent with the results of our study [ 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, they also found that both miR-503-5p and miR-424-5p could directly targeted KIF23 to inhibit OC development in vitro [ 69 ]. Additionally, Hu Y et al has reported that KIF23 could not only be used as a prognostic indicator for EOC, but also had a positive correlation with immune checkpoint protein, suggesting that it can be performed as a potential target for cancer immunotherapy, which is consistent with the results of our study [ 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…It seems that elevated of KIF23 expression is a common event in various human cancers. KIF23 was reported to be overexpressed in pancreatic ductal adenocarcinoma ( Gao et al, 2020 ), malignant pleural mesothelioma ( Kato et al, 2016a ), lung cancer ( Kato et al, 2016b ; Ye et al, 2017 ), breast cancer ( Zou et al, 2014 ), hepatocellular carcinoma (HCC) ( Sun et al, 2015 ; Cheng et al, 2020 ), gastric cancer ( Li X. L. et al, 2019 ; Liang et al, 2020 ), and ovarian cancer ( Li T. et al, 2019 ; Hu et al, 2020 ). Interestingly, most studies also showed that patients with higher KIF23 expression had worse prognosis survival compared to these with lower KIF23 expression ( Kato et al, 2016b ; Ye et al, 2017 ; Li T. et al, 2019 ; Li X. L. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Independent prognostic factors are often used as a part of prognostic monitoring and usually divided into clinical features and molecular biology.Common clinical features such as age, performance status, grade, Figo stage, and histology were considered independent prognostic factors for OC [ 49 , 50 ]. On the other hand, researchers found that low level of AK7, high expression of KIF23, P-gp protein, and SIX-gene signature(TGFBI, SFRP1, COL16A1, THY1, PPIB, BGN) could all be considered independent prognostic factors for OC [ 51 – 54 ]. In this study, we analyzed some clinical traits and found that age can be used as an independent prognostic factor for OC.However, grade and stage were not significant as independent prognostic factors of OC in our study,this may be due to differences in research data and experimental methods.At the same time, we added the score of risk calculated by the prognostic model for evaluation, and risk score was also an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%